Effectiveness of Online Learning During the Covid-19 Pandemic at SMA Negeri 4 Enrekang - Nasrullah, Muh.; Amalia, Riski; Sakawati, Herlina (Universitas Negeri Makassar, 2022)
This study aims to determine the effectiveness of online learning during the Covid-19 pandemic at SMA Negeri 4 Enrekang, Maiwa District, Enrekang Regency, and the factors that support and hinder online learning during the Covid-19 pandemic at SMA Negeri 4 Enrekang. This research is quantitative research with a descriptive approach. The population in this study were all students of SMA Negeri 4 Enrekang, totaling 478 students. With a sample of 48 people. Data collection techniques were carried out by observation, questionnaires, interviews, and documentation. As well as data analysis using the percentage formula. The results of this study indicate that the effectiveness of online learning during the Covid-19 pandemic at SMA Negeri 4 Enrekang, Maiwa District, Enrekang Regency with indicators, namely: The existence of material/content that is relevant to the learning objectives with a percentage reaching 75.76 percent, Using learning methods that are by the percentage of 76.77 percent, using learning media in various formats such as text, video, visual multimedia, and others with the percentage reaching 76.16 percent. Can occur synchronously and asynchronously with the percentage reaching 76.59 percent. Based on the results of the overall data analysis, the percentage results show 76.28 percent in the Effective category, and these results are in line with research in the field.